Aberrant Ulnar Artery and Ulnar Artery Thrombosis with Nerve Entrapment: A Case Report - Nickul N Shah; David Roman; Roland Purcell (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Introduction: Vascular compromise causes hand pain, and physical examination requires to differentiate vascular causes from isolated ulnar nerve compression. Diagnostic studies visualize vascular abnormalities such as CT scans, MRA scans, and AV fistulograms. Ulnar artery aneurysms are quite rare discoveries, related to repetitive trauma, vasculitis, anatomic abnormalities, or infections. It is essential to repair any aneurysm when flow impediment causes significant symptoms. Blunt injury to the ulnar artery and superficial palmar arch damages the arterial wall and forms an aneurysm. The sensory branch of the ulnar nerve becomes compressed. Treatment here is to resect the thrombotic segment to relieve the compression. It is interesting to note, in this particular case, that a high origin and superficial ulnar artery had coursed along the forearm and entered along the ulnar side of the hand. The presence of such anatomic variations are essential in medical practice. Case presentation: A 73-year-old Haitian female was admitted to the hospital with complaints of numbness and weakness along the right forearm and wrist. According to the patient's daughter, she has experienced these symptoms for at least two years' duration after minimal trauma to her right hand. Upon physical examination of the right wrist, a 3-cm palpable, pulsatile ulnar mass was found. The Allen's test showed no significant abnormalities, but the Tinel's test and pinprick examination were diminished. An AV fistulogram was scheduled the same day and a repair followed soon after. IV contrast dye demonstrated an aneurysm of the ulnar artery, along with an adjacent superficial branch. The decision was made to resect the aneurysm and allow the superficial ulnar artery remain patent for continuous blood supply to the 4th and 5th digits of her right hand. She was discharged the same day and to follow up in the vascular clinic a week later. Conclusion: This particular case describes a couple important disciplines that establishes further insight about the human anatomy, pathophysiology and vascular surgical management. First, hypothenar hammer syndrome has been illustrated in a patient without any history of vasculitis, infections, or congenital anatomic abnormalities. A diagnostic and therapeutic approach is necessary to relieve ulnar nerve entrapment. Second, this particular patient underwent a simple repair but it was found that an aberrant ulnar artery was discovered, which coursed adjacent and superficial to the aneurysm. It is important to establish an early diagnosis prior to any surgical procedures. Intraoperatively, proper identification to isolate and establish a continuous blood flow is essential. Knowledge of such variations allows for improved care in the fields of radiology, angiography, surgery and the medical sciences.